The spleen not taken: Differences in management and outcomes of blunt splenic injuries in teenagers cared for by adult and pediatric trauma teams in a single institution. Issue 3 (September 2017) - O'Connor, Sean C.; Doud, Andrea N.; Sieren, Leah M.; Miller, Preston R.; Zeller, Kristen A.
Abstract : BACKGROUND: Nonoperative management (NOM) of blunt splenic injury, initially touted for the care of pediatric patients, has become the standard of care for stable trauma patients of all ages. In our institution, trauma patients younger than 16 years are managed by the pediatric surgery service and patients 16 years or older are managed by the adult trauma service. Angioembolization is routinely used for adults with blunt splenic injury but rarely used for pediatric patients. A retrospective chart review was performed to determine if more liberal use of angioembolization increases the success rate of NOM of blunt splenic injury in adolescents. METHODS: Using our institutional trauma registry, we performed a retrospective chart review of 13- to 18-year-olds admitted with blunt splenic injury from 2007 to 2015. One hundred thirty-three patients were identified; 59 were 13- to 15-year-olds and cared for by the Pediatric Trauma service, whereas 74 were 16- to 18-year-olds and cared for by the Adult Trauma service. The cohorts were compared with respect to imaging performed, grade of injury, Injury Severity Score, presence of active extravasation or pseudoaneurysm, interventions performed, blood transfused, intensive care unit days, length of stay, complications, and 30-day mortality rates. RESULTS: There were no significant differences in Injury Severity Score, incidence of active extravasation or pseudoaneurysm identified on computed tomography, or grade of injury between the two cohorts. More patients underwent angioembolization in the "adult" group ( p = 0.001) with no difference in the success rate of NOM ( p = 0.117). The overall failure rate of NOM of high-grade injuries was only 4.1%. CONCLUSION: Failure of NOM in high-grade injuries is rare; as a result, the number needed to treat with prophylactic angioembolization would be around 37 patients, resulting in undue risk to many patients with no therapeutic benefit. No improvement in failure rate was seen with aggressive angioembolization, though a larger sample size is needed to rule out type 2 error. LEVEL OF EVIDENCE: Therapeutic, level IV.